A Body That Will Speak (TV Documentary; Public Service Brodcasting Trust, 2007) (2007)
A filmmaker, a university student, an entrepreneur and a radio jockey. Women who feel hungry, eat, grow fat and feel anxious about it. A film about not being perfect. A film about the never ending attempts to make the body “speak for the self in a meaningful and powerful way.” A journey to move beyond disorders and discover the real women battling the fantasies around and within them.
Keywords: DS Asia; HT Communities. Classes. Races; Gender; Body Image Disorders; India; Documentary Film